EDUCATION OF VALUES ACCORDING TO THE POINT OF VIEWS OF TEACHERS OF SOCIAL STUDIES - Hatice MEMİŞOĞLU (Fırat University, 2019)
Features gained through value education; raising awareness among children regarding their responsibilities toward themselves and their surroundings; ensuring that they gained awareness regarding the task assigned to them in establishing a next generations compatible in all surroundings such as home, school and etc.; learning how to cooperate with other members of society; realizing importance of paying attention to others’ opinion; and developing respect toward almost everything. Prominent objective of Social Sciences course is to raise citizens. In order to raise good citizens, first of all citizen who adopt national values, support universal values are * necessary to be raised. The aim of this study is to state the points of views of the teachers of Social Studies about education of values in Social Studies lessons. The qualitative research methods have been used to determine the teachers’ points of views. Twenty-seven teachers of Social Studies, working in thirteen secondary schools, points of views have been utilized. As a consequence of negotiation, content analysis method has been used for acquired data analysis. Data has been presented considering the questions of the negotiation. There are many exact citation to reflect views of Social Science teachers. According to the findings obtained, considering the views of Social Science Teachers about values included by Social Science Teachers in Social Science lessons, it has been seen that they include democratic values at the most and they include scientific values at the least. Researchers have indicated that teachers use modelling and value clarification approach from value approaches, narrative method from methods and case method when doing activities. When examining the opinions of Social Science Teachers about the issues related to training of values, they have mentioned about problems derived from textbooks and teachers much more.